2000
DOI: 10.1038/sj.leu.2401961
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcome through two decades in childhood ALL in the Nordic countries: the impact of high-dose methotrexate in the reduction of CNS irradiation

Abstract: In this population-based material from the five Nordic countries (Denmark, Finland, Iceland, Norway and Sweden), 2860 children below 15 years of age were diagnosed with acute lymphoblastic leukemia (ALL) from July 1981 to June 1998. The annual incidence was 3.9/100 000 children and was stable throughout the study period. The development from regional or national protocols to common Nordic treatment protocols for all risk groups was completed in 1992 through a successive intensification with multidrug chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
283
1
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(295 citation statements)
references
References 21 publications
(18 reference statements)
5
283
1
6
Order By: Relevance
“…Chart represents quantification of p-Thr308-Akt band intensity in relation to the total protein levels Materials and Methods Patients. The study included leukemic cells from two precursor-B ALL patients (2 boys, 13 and 16 years old), who were treated according to the NOPHO-ALL 2000 protocol, 36,37 and from 11 patients (5 males, 6 females) with CLL for whom the median age was 77 (50-85) years. The diagnosis was established according to the World Health Organization classification.…”
Section: Discussionmentioning
confidence: 99%
“…Chart represents quantification of p-Thr308-Akt band intensity in relation to the total protein levels Materials and Methods Patients. The study included leukemic cells from two precursor-B ALL patients (2 boys, 13 and 16 years old), who were treated according to the NOPHO-ALL 2000 protocol, 36,37 and from 11 patients (5 males, 6 females) with CLL for whom the median age was 77 (50-85) years. The diagnosis was established according to the World Health Organization classification.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the feasibility of reduced use of cranial irradiation, 4 emphasized that host pharmacogenetics influence the cure rate, 5 confirmed the importance of myelosuppression during maintenance therapy, 6 showed that MTX/6MP maintenance therapy is important for high-risk (HR) ALL, 7 and allowed mapping of the epidemiological and clinical characteristics of several cytogenetically defined subsets of ALL. [8][9][10][11][12][13][14] The goals of the subsequent common NOPHO ALL-2000 protocol were to examine the efficacy of Vincristine (VCR)/Dexamethasone reinductions during maintenance therapy and to examine the feasibility of non-centralized minimal residual disease (MRD) monitoring by flow cytometry and PCR.…”
Section: Introductionmentioning
confidence: 91%
“…3 During the following decade the therapy became harmonized, and since January 1992 Nordic children 1.0-14.9 years of age have been treated according to common protocols. The details and treatment results of two previous non-uniform protocol periods 1981-1985 and 1986-1991 were reported in the December 2000 issue of Leukemia together with those of 11 other study groups, 4 and their overall results are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Singlefraction TBI (sTBI) 10-12 Gy with CY (120 mg/kg) was used at the University Hospital in Huddinge during 1978-1995 and at the Helsinki University Hospital during [1978][1979][1980][1981][1982][1983]. Fractionated TBI (fTBI) was introduced in Helsinki in 1984 (10)(11)(12) Gy in 5-6 fractions) and in Huddinge in 1993 (12 Gy in 4 fractions). Patients with SAA have received CY (200 mg/kg) with or without TLI 6 Gy or fTBI 10 Gy.…”
Section: Treatment Characteristicsmentioning
confidence: 99%